On the management of land claims through tradable land dedication allowances - Hansjürgens, Bernd; Schröter, Christoph (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
The present article considers the idea to stop urban sprawl by introducing a tradable allowance system for the dedication of building land by the municipalities. It is suggested that the allowances should be created at the level of the central state and be distributed to the federal states, regions and municipalities. In this way the allowance system can benefit from the advantages of the well-established planning concepts at the regional and municipal level. The allocation effects of the tradable allowance system depend on the type of primary allocation, the economic strength of the trading municipalities, the use of auction proceeds and the development of regionally and functionally separated markets. It is recommended that the tradable allowance system should be integrated into an instrumental mix with an ecologically enhanced financial equalisation mechanism at the municipal level and an ecologically reformed real-estate tax.